Subject competency framework in fostering high-end lesson study – a case of teaching “properties of iron salts” unit in a senior high school - Wang, Lei; Wang, Quan; Kong, Simin; Hu, Jiuhua; Chen, Xiaoge (International journal for lesson and learning studies, 2022)
PurposeThis study aims to present a high-end lesson study (HELS) model to develop students' subject competency. Data were collected from a Beijing suburban key senior high school in China. How the subject competency framework (SCF) supports HELS and develops students' subject competency in practice are discussed in this study.Design/methodology/approachThis study provides a four-dimensional SCF developed by the chemistry education research team at Beijing Normal University. Basic procedures of the HELS model involve the project plan, students' pre-test, lesson design workshop, first-round teaching implementation and improvement, second-round teaching implementation and evaluation, students' post-test, and results discussion. Data were collected from each of the procedures, and analysis of the data is conducted in both qualitative and quantitative approaches.FindingsThe results show that the SCF supports HELS implementation by (1) identifying key teaching objectives based on curriculum standard requirements and students' subject competency performance; (2) organizing teaching content based on the core knowledge to develop cognitive mode; (3) designing tasks and activities regarding understanding–applying–transferring and innovating categories and sub-categories of SCF; (4) establishing students' cognitive perspectives and reasoning paths to promote their subject competency by teacher–student interaction.Originality/valueThe HELS model provides theory-based pedagogical guidance for conducting lesson studies. It presents the SCF and orientation. The SCF is used throughout the entire process of HELS, including the identification of teaching objectives, the selection and organization of teaching content, and the design and implementation of teaching activities. It reflects a systematic instructional design–implementation–discussion–improvement–evaluation process. The SCF-based HELS can be applied to different topics and disciplines.